Aspek Hukum dalam Penambangan Emas Skala Kecil dengan Penggunaan Merkuri dan Implikasinya terhadap Lingkungan dan Kesehatan: Studi Kasus di Desa Kalirejo, Kabupaten Kulonprogo - Sugasri Sugasri; Arif Rahman Hakim (Riviera Publishing, 2025)
Small-scale gold mining (SSGM) using mercury remains prevalent in several regions of Indonesia, including Kalirejo Village, Kulonprogo Regency. This practice poses significant legal, environmental, and health issues. This study aims to analyze the legal aspects of SSGM, particularly concerning environmental regulations, public health protection, and the legal responsibility of miners. A normative juridical approach combined with a field case study was used to examine mercury usage practices, their impacts, and law enforcement at the local level. The findings reveal that although regulations such as Law No. 32 of 2009 on Environmental Protection and Management and Ministry of Environment Regulation No. 29 of 2013 on Emission Standards exist, their enforcement remains weak in practice. Mercury use has been proven to degrade environmental quality, contaminate soil and water, and cause severe health problems such as neurological disorders and organ damage in surrounding communities. This study emphasizes the importance of strengthening law enforcement, providing mercury-free gold processing technologies, and raising public awareness as mitigation measures.